The birth of the Palestinian refugee problem revisited - Morris, Benny, 1948- (Cambridge Middle East studies, 2004)
While the focus remains on the 1948 war and the analysis of the Palestinian exodus, this edition contains more information about what happened in Jerusalem, Jaffa and Haifa, and how events there led to the collapse of Palestinian urban society.